The Impact of Different Nanoparticle Concentrations Combined with Gamma Rays on Breast Cancer Cells - Fadhil , Noor Kh.; Dawood, Numan S.; Al-Khalisy, Maan H. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Cancer is the greatest cause of death worldwide. To treat cancer effectively, radiation must maximize cytotoxicity against tumor cells while limiting injury to healthy cells. Nanotechnology and biomedical technologies can help improve cancer detection and treatment, but they also create challenges.Objective: The objective of the study is to evaluate the effect of different concentrations of gold nanoparticles (25%, 50%, 100%) exposed to different doses of gamma radiation (200Gy, 400Gy, 600Gy) on breast cancer cells in women and comparison with normal cells. Method: For 24 and 48 hours, breast cancer and normal breast cells were treated to 25%, 50%, and 100% gold nanoparticles (AuNPs). Another comparable method was done after exposing concertation AuNPs to 200Gy, 400Gy, and 600Gy gamma radiation. After 24 and 48 hours, the results were compared REF and MDA values.Results: Significant changes in cell growth suppression between MDA and REF after 24 and 48 hours, were seen with AuNPs alone (25%, 50%, 100% concentration) and with gamma ray dosages 200Gy, 400Gy, 600Gy. The mean growth inhibition of cells treated with AuNPs irradiated by gamma rays (200Gy, 400Gy, 600Gy) compared to AuNPs alone was highly significant (P